A Kerr magnetometer setup in the kHz regime based on open-hardware architecture (2019)
A high sensitivity Kerr magnetometer (?I/I = 1/30) is presented, making use of open source hardware and software. By making time resolved measurements (up to 0.15 s/cycle) the signal quality has been greatly improved up to an order of magnitude, enabling us to compare our measurements with commercial vibrating sample magnetometers. We also present an additional setup to amplify the Kerr signal in a 25:1 scale, cleaning a large part of the electronic and trigger noise. © Published under licence by IOP Publishing Ltd.